Identification of Moss Types in the UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan Area - Lia Junita Harahap (Institut Agama Islam Negeri, 2023)
Moss is a division of lower plants that is usually found in damp and dry places. Moss usually has a characteristic green color, is small in size and has various shapes. Based on ecology, mosses have an important relationship with the ecosystem, namely maintaining water balance and nutrient cycles, being an important habitat for other organisms, being able to act as bioindicators because mosses are more sensitive to climate change and are pioneer plants. Because moss has an important role in the environment and research has never been carried out and there is no data regarding the identification of moss in the UIN Syahada Padangsidimpuan area. So the aim of the research was to identify the moss that grows in the area. This research uses qualitative descriptive research using exploratory methods. The research results obtained were 15 species of moss consisting of 10 species of leaf moss, 3 species of liverwort and 2 species of lichenese